Post-traumatic Stress Disorder Post Partum - Schwab, W.; Marth, C.; Bergant, A. M. (Geburtshilfe und Frauenheilkunde, 2012)
Traumatic birth experiences may lead to serious psychological impairment. Recent studies show that a considerable number of women can develop post-traumatic stress disorder (PTSD), in some cases in a subsyndromal form. Until now, the possibility that postpartum psychological symptoms might be a continuum of a pre-existing disorder in pregnancy has rarely been considered. This study therefore aimed to evaluate the proportion of women who develop post-traumatic stress disorder as a result of childbirth. Materials and Methods: 56 multiparous women were recruited for the study. The diagnosis of PTSD was made according to the criteria for psychological disorders in the DSM-IV (Diagnostics and Statistical Manual of Mental Disorders). The data were collected in structured interviews in the 30th to 38th week of gestation and in the 6th week post partum. Results: Of the 56 women participating, 52 (93 %) completed the survey. Uncontrolled results showed that 21.15 % of the multiparous women met the full diagnostic PTSD criteria in the 6th week post partum. After the exclusion of all cases already characterised by all criteria or a subsyndromal form of PTSD caused by previous traumatisation, the PTSD rate was below 8 % at 6 weeks postpartum (= incidence rate of PTSD post partum). Conclusions: The present study is the first prospective longitudinal study to demonstrate the occurrence of full criteria PTSD in multiparous women as a result of childbirth after having excluded pre-existing PTSD. The results of our study show a high prevalence rate of PTSD during pregnancy. A number of women report all aspects of post-traumatic stress disorder as a result of childbirth.
Keywords: childbirth; post-traumatic stress disorder; multiparous women; incidence; pre-existing PTSD